Asuhan Keperawatan Gerontik Pada Pasien Hipertensi Dengan Intervensi Pemberian Jus Semangka Untuk Menurunkan Tekanan Darah Tinggi Di Periuk - Restika Muji Chitra; Siti Robeatul Adawiyah; Hasan Basri (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Background: Elderly is a period where the organism has reached a period of anxiety or peak in function, size and some have shown a decline in body function over time, physiological function has decreased due to the aging process so that hypertension appears. There are two ways to reduce hypertension, pharmacological and non-pharmacological. Non-pharmacological can be done by giving watermelon juice to reduce high blood pressure in patients. Purpose: The purpose of this paper is to determine the effectiveness of watermelon juice in reducing high blood pressure in the elderly in Periuk. Method: Case study design using nursing care. The case study sample uses 1 patient. Results: Based on the results of implementation on Mrs. S by applying watermelon juice therapy for 3 days, her high blood pressure decreased, which was obtained after implementing watermelon juice on Mrs. S who has hypertension health problems. On Thursday, January 4 2024 at 10.00 WIB, watermelon juice was implemented with the evaluation results, namely Mrs. S 146/90 mmHg. On Friday, January 5 2024 at 10.00 WIB, watermelon juice was implemented again with the evaluation results, namely Mrs. S 139/89 mmHg. On Saturday, January 6 2024 at 10.00 WIB, watermelon juice was implemented again with the evaluation results, namely Mrs. S 130/80 mmHg, so that the diagnosis of ineffective health maintenance nursing can be concluded by changes towards improvement. This shows the influence of giving watermelon juice to reduce high blood pressure.